Development of a 50K SNP Array for Japanese Flounder and Its Application in Genomic Selection for Disease Resistance. (March 2021) - Zhou, Qian; Chen, Ya-dong; Lu, Sheng; Liu, Yang; Xu, Wen-teng; Li, Yang-zhen; Wang, Lei; Wang, Na; Yang, Ying-ming; Chen, Song-lin
Abstract: Single nucleotide polymorphism (SNP) arrays are a powerful genotyping tool used in genetic research and genomic breeding programs. Japanese flounder ( Paralichthys olivaceus ) is an economically-important aquaculture flatfish in many countries. However, the lack of high-efficient genotyping tools has impeded the genomic breeding programs for Japanese flounder. We developed a 50K Japanese flounder SNP array, "Yuxin No. 1, " and report its utility in genomic selection (GS) for disease resistance to bacterial pathogens. We screened more than 42.2 million SNPs from the whole-genome resequencing data of 1099 individuals and selected 48 697 SNPs that were evenly distributed across the genome to anchor the array with Affymetrix Axiom genotyping technology. Evaluation of the array performance with 168 fish showed that 74.7% of the loci were successfully genotyped with high call rates (> 98%) and that the polymorphic SNPs had good cluster separations. More than 85% of the SNPs were concordant with SNPs obtained from the whole-genome resequencing data. To validate "Yuxin No. 1" for GS, the arrayed genotyping data of 27 individuals from a candidate population and 931 individuals from a reference population were used to calculate the genomic estimated breeding values (GEBVs) for disease resistance to Edwardsiella tarda . There was a 21.2% relative increase in the accuracy of GEBV using the weighted genomic best linear unbiased prediction (wGBLUP), compared to traditional pedigree-based best linear unbiased prediction (ABLUP), suggesting good performance of the "Yuxin No. 1" SNP array for GS. In summary, we developed the "Yuxin No. 1" 50K SNP array, which provides a useful platform for high-quality genotyping that may be beneficial to the genomic selective breeding of Japanese flounder.